KESEDIAAN BALAI BESAR PENDIDIKAN DAN PELATIHAN KESEJAHTERAAN SOSIAL (BBPPKS) DALAM MENANGANI HIV/AIDS - Hakim, Moch Zaenal (Sekolah Tinggi Kesejahteraan Sosial (STKS) Bandung, 2012)
Abstract As an institution in providing training for social workers, Balai Besar Pendidikan dan Pelatihan Kesejahteraan Sosial (BBPPKS) has a very important role to play towards the social well-being of the community. A qualitative study was conducted in order to identify the extent of BBPPKS’s involvement in providing training on HIV/AIDS. Aspects which is tested including the profile of BPPKS institution; the institutional assessment concerning HIV/AIDS from the aspects of knowledge, attitudes toward people with HIV/AIDS (PLWHA); policy and requirement of HIV/AIDS training; and HIV/AIDS training curriculum for social worker. With purposive and snowball sampling technique, six institutions throughout Indonesia under the BBPPKS were selected as informants. Results showed that informant had a good understanding about HIV/AIDS and have positive attitudes towards PLWHA. With regards to the training needs of HIV/AIDS for social workers, the BBPPKS in Jayapura understands the problems of HIV/AIDS and has conducted training on HIV/AIDS for their social workers and stakeholders in this region. However, the other five institutions of BBPPKS, namely Padang, Bandung, Yogyakarta, Makassar and Banjarmasin have yet to acknowledge the problems of HIV/AIDS in their areas. Furthermore, the five institutions do not have a training program of HIV/AIDS for social workers. At the same time, the five BBPPKS highlighted that currently there is no stakeholders in the province ever propose for HIV/AIDS training for social workers. However, results of research showed that there is an important need for HIV/AIDS training. Other factors which cause these institutions for not having any training programs include that there are no curriculum on HIV/AIDS to train the social workers, there are no competent trainers in this area and is not a top priority from the Ministry of Social Affairs of Indonesia to have such training. This study also introduced a curriculum on HIV/AIDS training for social workers which can be implemented by BBPPKS.Keywords: BBPPKS, social worker, stakeholders, training programme, curriculum on HIV/AIDS training for social worker Abstrak Peranan Balai Besar Pendidikan dan Pelatihan Kesejahteraan Sosial (BPPKS) sangat penting dalam meningkatkan kesejahteraan sosial masyarakat. Penelitian kualitatif ini dilakukan untuk mengetahui sejauhmana BBPPKS terlibat dalam pelatihan tentang HIV/AIDS. Aspek-aspek kajian meliputi profil BBPPKS; penilaian institusi terhadap HIV/AIDS berdasarkan aspek pengetahuan, sikap terhadap ODHA, kebijakan dan keperluan pelatihan HIV/AIDS, serta kurikulum pelatihan HIV/AIDS untuk pekerja sosial. Dengan menggunakan teknik purposive dan snowball sampling, enam BBPPKS di Indonesia telah dipilih sebagai informan. Hasil penelitian menunjukkan informan mempunyai pemahaman yang baik tentang HIV/AIDS dan sikap yang positif terhadap ODHA. Terkait dengan kebutuhan latihan HIV/AIDS untuk pekerja sosial, BBPPKS Jayapura memahami permasalahan HIV/AIDS dan telah menjalankan latihan HIV/AIDS untuk pekerja sosial dan stakeholder di wilayah kerjanya. Lima institusi lainnya yaitu BBPPKS Padang, Bandung, Yogyakarta, Makassar dan Banjarmasin belum dapat memahami permasalahan HIV/AIDS dengan baik di wilayah kerjanya. Kelima institusi ini juga belum mempunyai program latihan HIV/AIDS untuk pekerja sosial. Kelima BBPPKS juga berpendapat belum ada stakeholder di wilayah kerjanya yang mengusulkan latihan HIV/AIDS untuk pekerja sosial. Namun demikian, hasil penelitian menunjukkan sudah ada kebutuhan latihan HIV/AIDS. Faktor-faktor lain yang menyebabkan BBPPKS belum mempunyai program latihan, yaitu ketiadaan kurikulum latihan HIV/AIDS untuk pekerja sosial, tidak ada tenaga pengajar yang kompeten melatih HIV/AIDS, dan belum ada keutamaan dalam program latihan HIV/AIDS dari Kementerian Sosial Indonesia. Kajian ini juga merekomendasikan satu kurikulum latihan HIV/AIDS khusus pekerja sosial untuk diimplementasikan oleh BBPPKS di Indonesia.